Cracked Tooth Syndrome as a major issue of today’s patients – review of literature - Jurczykowska, Marta; Muñoz-Sandoval, Cecilia; Szabelska, Anna; Chałas, Renata (Journal of Stomatology, 2015)
Introduction. Vertical fractures and cracks of teeth are a frequent problem during daily dental clinical practice. Therefore, there is a need to determine patterns of diagnostics, therapy, and preventive management in these cases because dental fractures and cracks, depending on their severity, may lead to many undesirable consequences. Aim of the study. To present symptomatology of Cracked Tooth Syndrome (CTS), characteristics of the diagnostic process and therapeutic methods based on literature. Results. The review revealed that Cracked Tooth Syndrome is a frequent occurrence and diagnostic methods with a big probability allow for correct recognition of CTS. Conclusion. To prevent the progress of CTS proper diagnostic order should be maintained and earlytherapeutic protocol implemented.